Flaxseed extract induces apoptosis in human breast cancer MCF-7 cells. (May 2019) - Hu, Tingyan; Linghu, Kegang; Huang, Siqi; Battino, Maurizio; Georgiev, Milen I.; Zengin, Gokhan; Li, Defang; Deng, Yun; Wang, Y.T.; Cao, Hui
Abstract: Significant evidence indicated that flaxseed ( Linum usitatissimum ) possesses various positive health aspects such as reducing the risk of cancer and cardiovascular diseases. The fatty acids are considered to be responsible for these benefits of flaxseed. Herein, the in vitro effects of flaxseed extract on the growth and apoptosis of human breast cancer MCF-7 cells were investigated. The MCF-7 cells treated with flaxseed extract showed a dose-dependent decrease in cell viability. The flaxseed extract induced reactive oxygen species and the flow cytometric analysis demonstrated that flaxseed fatty acids triggered apoptosis of MCF-7 cells, which was also shown by the loss of mitochondrial membrane potential and caspase cascade reaction. Thus, the flaxseed extract regulated the growth of MCF-7 cells and induced apoptosis. Eventually, the flaxseed could be used as a dietary supplement to prevent breast cancer.